Influence of Temperature on the Performance of LiNi1/3Co1/3Mn1/3O2 Prepared by High-Temperature Ball-Milling Method - Ming Tian; Xuetian Li; Zhongbao Shao; Fengman Shen (Advances in Materials Science and Engineering)
Aiming at the preparation of high electrochemical performance LiNi1/3Co1/3Mn1/3O2 cathode material for lithium-ion battery, LiNi1/3Co1/3Mn1/3O2 was prepared with lithium carbonate, nickel (II) oxide, cobalt (II, III) oxide, and manganese dioxide as raw materials by high-temperature ball-milling method. Influence of ball-milling temperature was investigated in this work. It was shown that the fine LiNi1/3Co1/3Mn1/3O2 powder with high electrochemical performance can be produced by the high-temperature ball-milling process, and the optimal ball-milling temperature obtained in the current study was 750°C. Its initial discharge capacity was 146.0 mAhg−1 at the rate of 0.1 C, and over 50 cycles its capacity retention rate was 90.2%.